Enhancing Temperature Sensitivity Using Cyclic Polybutylene Terephthalate- (c-PBT-) Coated Fiber Bragg Grating - Ahmad, Harith; Noor, S.F.S.M.; Arusin, A.F.; Samsudin, S.A.; Thambiratnam, Kavintheran; Chong, Wu Yi; Lim, Kok Sing; Zulkifli, Mohd Zamani (Hindawi Publishing Corporation, 2018)
A polybutylene terephthalate (c-PBT) coating for enhancing the temperature sensitivity of a fiber Bragg grating- (FBG-) based sensor is proposed and demonstrated. The coating is seen to increase the sensitivity of the proposed sensor by a factor of approximately 11 times as compared to a bare FBG, giving a Bragg wavelength shift of 0.11 nm/°C with an operating temperature ranging from 30°C to 87°C. The proposed sensor is also easy to fabricate as compared to other similarly coated FBG sensors, giving it a significant advantage for field applications with the added advantage of being easily reformed to fit various housings, making it highly desirable for multiple real-world applications.